Nước dưới đất trong cồn cát ven biển phía nam Quảng Bình và định hướng khai thác sử dụng - Tặng, Nguyễn Xuân (Vietnam Journal of Earth Sciences, 2018)
Groundwater in coastal sand dune area in the south of Quang Binh province and posibility for exploitation